Power and landscape in Atlantic West Africa : archaeological perspectives - Monroe, J. Cameron; Ogundiran, Akinwumi (New York : Cambridge University Press, 2012)
"This volume applies insights drawn from the theories and methods of landscape archaeology to contribute to our understanding of the nature if West African societies in the Atlantic Era (17th-19th Centuries AD). The authors adopt a broad set of methods and approaches to tackle how the nature and structures of African political and social relations changed across regions in this period. This is only the second volume in a decade to focus on the archeology of this period in West Africa, and the first volume in sub-Saharan Africanist archeology to be focused in the recent past in one sub-region of the continent from a coherent methodological and theoretical standpoint"--Provided by publisher.
Power and landscape in Atlantic West Africa / J. Cameron Monroe and Akinwumi Ogundiran -- Atlantic impacts on inland Senegambia : French penetration and African initiatives in eighteenth- and nineteenth-century Gajaaga and Bundu (Upper Senegal River) / Ibrahima Thiaw -- Political transformations and cultural landscapes in Senegambia during the Atlantic era : an alternative view from the Siin (Senegal)? / François Richard -- The Eguafo polity : between the traders and raiders / Sam Spiers -- From the shadow of an Atlantic citadel : an archaeology of the Huedan countryside / Neil L. Norman -- Segou, slavery, and sifinso / Kevin C. MacDonald and Seydou Camara -- Building the state in Dahomey : power and landscape on the Bight of Benin / J. Cameron Monroe -- The formation of an Oyo imperial colonial enclave during the Atlantic age / Akinwumi Ogundiran -- The rise of the Bassar chiefdom in the context of Africa's internal frontier / Philip de Barros -- Fortified towns of the Koinadugu Plateau : northern Sierra Leone in the pre-Atlantic and Atlantic worlds / Christopher R. DeCorse -- Rethinking the Mandara political landscape : cultural developments, climate, and an entry into history in the second millennium AD / Scott MacEachern -- The local and the global : historiographical reflections on West Africa and the Atlantic age / Ray A. Kea.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 6, 2025).
eBooks on EBSCOhost
Keywords: Africa, West -- History -- To 1864.; Social structure -- Africa, West -- History; Political culture -- Africa, West -- History; Africa, West -- Commerce -- Social aspects -- History; Africa, West -- Commerce -- Political aspects -- History; Landscape archaeology -- Africa, West; Structure sociale -- Afrique occidentale -- Histoire; Afrique occidentale -- Commerce -- Aspect social -- Histoire; Afrique occidentale -- Commerce -- Aspect politique -- Histoire; Archéologie du paysage -- Afrique occidentale; SOCIAL SCIENCE -- Archaeology; HISTORY -- Africa -- West; Commerce -- Political aspects; Commerce -- Social aspects; Landscape archaeology; Political culture; Social structure; West Africa; Soziokultureller Wandel; Wirtschaftsentwicklung; Anthropogeografie; Sklavenhandel; Archäologie.; Gesellschaft; Landschaft; Westafrika; Westafrika; To 1864; History